"Fiabe magiche in forma drammatica": la fortuna delle opere di Carlo Gozzi in Ungheria - Dombi, Anikó (Verbum – Analecta Neolatina, 2012)
Although Carlo Gozzi was not a very popular theatre author, his works were staged in Hungary quite early, a few years after their publication from the 1780’s. His works arrived in Hungary through a German influence, his dramas were translated into and staged in German in the Deutsche Theater ’German Theatre’ of Pest and Buda. The first performance of a Gozzi play took place in 1783. His most popular drama was Turandot, an adaptation of Schiller’s work, which was frequently played in the German Theatre. The first production in Hungarian occurred in 1837 in the Castle Theatre. The company staged Turandot, and it was a great success. In spite of the success, Gozzi’s plays were not well received by the critics. In this paper, I discuss some examples of the critical reception of Carlo Gozzi and his plays.